High watermarking capacity based on spatial domain technique - Zeki, Akram M.; Abdul Manaf, Azizah; Mahmod, Shayma S. (Asian Network for Scientific Information, 2011)
Watermarking capacity refers to the amount of information we are able to insert into the image. Low signal to noise ratio is a phenomenon of watermarking channels, which severely limits the capacity. The aim of this study is to develop a digital watermarking model, which can find out the possibility to embed maximum amount of data in an image without degrading the quality of watermarked image. In this approach, the host image will be partitioned into non-overlapping blocks and passing an imaginary plane in the three critical pixels. The characteristics of this plan should not be changed after embedding message; then the same characteristics will be used to evaluate the embedded capacity in the extracting module.